On the Electro‐Optics of Carbon Stack Perovskite Solar Cells. Issue 2 (26th July 2019) - Kerremans, Robin; Sandberg, Oskar J.; Meroni, Simone; Watson, Trystan; Armin, Ardalan; Meredith, Paul
Abstract : Mesoporous carbon stack architecture is attracting considerable interest as a candidate for scalable, low‐cost perovskite solar cells amenable to high‐throughput manufacturing. These cells are characterized by microns‐thick mesoporous titania and zirconia layers capped by a nonselective carbon electrode with the whole stack being infused with a perovskite semiconductor. Although the architecture does not deliver the >20% power conversion efficiencies characteristic of perovskite planar and mesoporous geometries, it does produce cells with respectable efficiencies >16%, which is unexpected due to the carbon electrode being a nonideal anode and the active layers being so thick. Optimization of these cells requires an understanding of the coupled efficiencies of light absorption, charge generation, and extraction which is currently unavailable. Herein, a combined experimental‐simulation study that elucidates photogeneration and extraction is reported. By determining the optical constants of the individual components and using effective‐medium approximations, the internal quantum efficiencies (IQE) in both the titania and zirconia layers are determined to be ≈85%. Numerical drift‐diffusion simulations indicate that this high IQE is a consequence of the thick junctions reducing minority carrier concentrations at the electrodes, thereby decreasing surface recombination. This insight can now be used to tune the carbon stack for efficiency and simplicity. Abstract : Carbon stack perovskite solar cells offer potential as a manufacturable architecture using techniques such as screen printing and are characterized by micron‐scale thick active junctions. Herein, an electro‐optical model is developed that explains the working mechanisms of charge generation and collection in these solar cells that not only provides deep insight but also can be used for device optimization.